2014
DOI: 10.4161/biom.29507
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic force microscopy

Abstract: Magnetic force microscopy (MFM) is an atomic force microscopy (AFM) based technique in which an AFM tip with a magnetic coating is used to probe local magnetic fields with the typical AFM spatial resolution, thus allowing one to acquire images reflecting the local magnetic properties of the samples at the nanoscale. Being a well established tool for the characterization of magnetic recording media, superconductors and magnetic nanomaterials, MFM is finding constantly increasing application in the study of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 98 publications
(124 reference statements)
1
41
0
Order By: Relevance
“…Magnetic force microscopy (MFM) proved to be a promising technique to successfully image clusters of small superparamagnetic nanoparticles without labelling and provides all the information described above in a single pass [7][8][9][10][11]. Recent investigations demonstrate the capability of MFM for biological systems e. g. to evaluate the iron distribution in biological tissues [12] and to study the cellular uptake of magnetic nanoparticles [13]. Nevertheless the interaction of the probe with nanoparticles is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic force microscopy (MFM) proved to be a promising technique to successfully image clusters of small superparamagnetic nanoparticles without labelling and provides all the information described above in a single pass [7][8][9][10][11]. Recent investigations demonstrate the capability of MFM for biological systems e. g. to evaluate the iron distribution in biological tissues [12] and to study the cellular uptake of magnetic nanoparticles [13]. Nevertheless the interaction of the probe with nanoparticles is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for successful MFM imaging, the sample is first scanned in the close range where the Van der Waals forces are dominant to acquire a topographical image and then the tip is lifted to a region where the magnetic forces are dominant and scanned for MFM image. This technique is advantageous as it minimizes the effects caused by non-magnetic forces and ensures only the record of magnetic forces [226,227]. The use of MFM in biopolymer systems is marginally explored and is limited to the analysis of magnetic biocomposites [83,[228][229][230][231].…”
Section: B) Chemical Force Microscopymentioning
confidence: 99%
“…MFM study of the surface of SPION nanocomposites showed that the distribution of SPIONs in a matrix can create domains in the nanocomposite . The high potential of MFM for biological and medical applications has been shown, for example, by visualization the iron core of ferritin as well as by studying the cellular uptake of SPIONs . Wang et al mapped the uptake of SPIONs into tumor cells and determined the intracellular iron content and spatial distribution of the intracellular iron .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al mapped the uptake of SPIONs into tumor cells and determined the intracellular iron content and spatial distribution of the intracellular iron . Passeri et al investigated the use of superparamagnetic core shell nanoparticles for cell labeling in vitro . Both Zhang et al and Passeri et al emphasize that the quantification from MFM images of depth information under the cell membrane is still challenging and further investigations and simulations are necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation